تحديد ثلاثة أنواع من جنس الشعريات الطفيلية parasitic Capillaria ( ديدان خيطية Nematoda) في لمعة أمعاء أسماك الكارب, في مزرعة شطحا (الغاب- سوريا) - سلمان حسن (Latakia University Journal -Biological Sciences Series, 2019)
شملت الدراسة 142 فردا من أسماك الكارب العادي Cyprinus carpio L. تراوح أعمارها بين 35 يوما والسنة، أخذت العينات بشكل عشوائي, شهريا, من مزرعة شطحا (الغاب), خلال العام 2006. تم عزل ثلاثة أنواع من الديدان الخيطية وتصنيفها, تنتمي تصنيفيا إلى الجنس Capillaria (C.) هي: Capillaria tomentosa , Capillaria amurensis and Capillaria baicalensis, وجدت في القسم الأمامي من لمعة الأمعاء، وسجل النوع C.baicalensis لأول مرة في سوريا, في دراستنا هذه. اختلفت الأنواع السابقة في نسب خمجها ( إصابتها) للأسماك, وكان النوع C.tomentosa الأكثر انتشارا, بنسبة إصابة, بلغت 8،58%, وشدة إصابة, بلغت 1،78 دودة/سمكة. أبدت هذه الطفيليات علاقة مباشرة بالحرارة, بوصفها مؤشراً بيئياً, لا حيوياً. Study was performed on 142 carp fish (Cyprinus carpio L.) aged between 35 days to one year old. Samples were collected randomly, and monthly from Shatha fish farms. Isolation and classification were made for three parasitic species of Nematoda which were Capillaria tomentosa , Capillaria amurensis and Capillaria baicalensis deposited in anterior fragment of intestinal lumen. The third species was recorded for the first time in Syria at Shatha fish farm in this study. These species were varied in rate of their fish infection, whereby Capillaria tomentosa was the more distributed one in infection rate 8,58% and infection intensity 1,78 worm/fish. Parasites have shown direct relationship with temperature as non-biotic environmental factor.